FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PEKERJA MANUFAKTUR KEMASAN MINUMAN DI JAKARTA TIMUR TAHUN 2022 - Rafif Priyambodo Prakoso (2022)
Opportunities for stress can occur anytime and anywhere, one of which is at work. Workers who experience work stress will greatly affect their performance and company productivity. Manufacturing is one place that has the potential to trigger work stress. The purpose of this study is to analyze the determinants of work stress on Beverage Packaging Manufacturing workers in East Jakarta in 2022. This research method is quantitative analytic with a cross-sectional study design and total sampling was chosen for a sample of 75 respondents. The measuring instruments used are The Workplace Stress Scale, NIOSH Generic Job Stress, body mass index, and Cardiovascular Load. The statistical test used is the Chi-square test. The results of the analysis showed that age (p-value = 0.016, POR=4,5), work shift (p-value = 0.000, POR=13,5), social support (p-value = 0.016, POR=4,5), and physical workload (p-value = 0.000, POR=20,44) had a significant assosiation with work-related stress. Therefore, workers are advised to establish good communication and support each other. Companies can make training so that workers have more experience in their fields, do team building, and add tools or machines to the company.